Pengerasan Telinga Ganda Kronis: Laporan Kasus Dermatitis Kontak Iritan yang Menyerupai Lepra : Laporan Kasus - Alika, Maria Ulfa Noor; Hartanto, Felix (PT Kalbe Farma Tbk., 2025)
Introduction: Irritant contact dermatitis (ICD) is an inflammatory cutaneous disorder induced by the breakdown of the barrier and activation of innate immune responses. In the chronic stage, plaques thicken and cause scaling, hyperkeratosis, fissures, rhagades,and/or lichenification. Case: A 34-year-old male presented with both earlobe thickening and minor numbness, particularly whilesweating or being exposed to direct sunlight. Physical examination revealed erythematous patches, as well as edema and thickness of both earlobes. Patch test and slit skin smears yielded negative findings, ruling out allergic contact dermatitis (ACD) and leprosy. The diagnosis of irritant contact dermatitis was caused by sweat and sun exposure. The treatment consisted of twice daily ofdesoximethasone and mupirocin cream, and 10 mg loratadine once daily. Discussion: ICD is an inflammatory cutaneous disorder induced by the breakdown of the skin barrier and the activation of the innate immune response. Thickening and numbness of both earlobes are caused by repetitive irritation from sweat and sunlight exposure over time. Conclusion: Irritant contact dermatitis in both earlobes should be differentiated from other skin diseases, particularly leprosy.